Employees Perception on Performance Appraisal Effectiveness in The Cyprus Public Sector (EAC) - Petasis, Andreas; Christodoulou, Stylianos; Louca, Alexia (IJHCM (International Journal of Human Capital Management), 2020)
Performance appraisals are important for effective evaluation and management of personnel. This research investigates the Electricity Authority of Cyprus’ employees’ perceptions of performance appraisal. Data were collected from 161 employees of the Organization, using an online semi-structured questionnaire, and analyzed using SPSS; the qualitative data were analyzed manually. The results of the study highlighted respondents’ perceptions with regard to the Organization’s performance management practices, which have a created a culture of mistrust towards the performance management system in use. The Organization’s present performance appraisal system seems to posit more shortcomings than strengths and it doesn’t seem to be integrated or linked with the organizational goals and missions of the Authority’s. The research has delivered some information on what needs to be changed in order to improve the current system. The findings have serious managerial implications for redesigning the performance appraisal system so as to be more effective, more credible and more transparent. These implications include actions towards introducing new methods, training the appraisers, increasing motivation and provision of resources for effective performance appraisal.